2016
DOI: 10.1371/journal.pone.0149265
|View full text |Cite
|
Sign up to set email alerts
|

The Tocotrienol-Rich Fraction Is Superior to Tocopherol in Promoting Myogenic Differentiation in the Prevention of Replicative Senescence of Myoblasts

Abstract: Aging results in a loss of muscle mass and strength. Myoblasts play an important role in maintaining muscle mass through regenerative processes, which are impaired during aging. Vitamin E potentially ameliorates age-related phenotypes. Hence, this study aimed to determine the effects of the tocotrienol-rich fraction (TRF) and α-tocopherol (ATF) in protecting myoblasts from replicative senescence and promoting myogenic differentiation. Primary human myoblasts were cultured into young and senescent stages and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
47
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 48 publications
(73 reference statements)
11
47
2
Order By: Relevance
“…An adjusted data according to plasma concentration and daily intake showed a strong correlation between γTF and muscle strength, as well as a significant correlation between αTF and both measurements [207]. Although this study only focused on the effects two types of TF on muscle strength, several experimental studies examining the antioxidant effects of T3 have found that T3 was superior due to their better distribution in the lipid layers of the cell membrane [199,208]. Thus, T3 may act as a better antioxidant than TF.…”
Section: Effects Of Tocotrienol On Muscle Diseasesmentioning
confidence: 87%
See 1 more Smart Citation
“…An adjusted data according to plasma concentration and daily intake showed a strong correlation between γTF and muscle strength, as well as a significant correlation between αTF and both measurements [207]. Although this study only focused on the effects two types of TF on muscle strength, several experimental studies examining the antioxidant effects of T3 have found that T3 was superior due to their better distribution in the lipid layers of the cell membrane [199,208]. Thus, T3 may act as a better antioxidant than TF.…”
Section: Effects Of Tocotrienol On Muscle Diseasesmentioning
confidence: 87%
“…It was also shown to reverse senescence in stress-induced pre-senescence myoblasts, demonstrating the potential therapeutic effects of TRF on senescent muscle cells [198]. Furthermore, Khor et al suggested that TRF was superior to αTF in promoting myogenic differentiation followed by prevention of replicative senescence of myoblasts [199].…”
Section: Effects Of Tocotrienol On Muscle Diseasesmentioning
confidence: 99%
“…Cells were cultivated at 37°C in a humid atmosphere containing 5% CO 2 . After that, the myoblasts were expanded extensively to reach replicative senescence, which was manifested by the decline in proliferative capacity and accumulation of senescence biomarker in culture [15]. For each passage, the population doubling (PD) of cells was calculated as: ln(N/n)/In2, where N is the number of cells at harvest stage and n is the number of cells at seeding stage.…”
Section: Cell Culture and Replicative Senescencementioning
confidence: 99%
“…Replicative senescence affects myogenic differentiation in myoblasts resulting in the production of impaired myotubes [14]. The expression of the factors regulating myogenic differentiation, such as myogenic regulatory factors (MRFs), is deregulated in senescent myoblasts [15,16]. The MRFs, which include Myf5, MyoD, myogenin and MRF4, are the key transcription factors in the myogenic specification, differentiation and maintenance [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation